Przestrzenne zróżnicowanie starzenia się ludności w Polsce a płodność - Podogrodzka, Małgorzata (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2014)
The text aims at describing spatial distribution of people aged 60+ in Poland between 1991–2011 and showing correlation between aging of society and fertility. The analysis revels that in those regions of Poland where the number of people aged 60+ is highest, the fertility rate is lowest, however important differences between regions and in time were observed. Therefore no common and unvarying pattern was observed.